Enhancing the potential of SMEs by using European funds in Romania - Simona MASCU; Manuela Liliana MURESAN (Revista de Management Comparat International)
The main objective of this article is the detailed approach of different concepts regarding the importance of small and medium enterprises in the contemporary economy in Romania, their role, place and specificity on the international markets. The analysis focuses on the current state of SMEs in Romania, both from a perspective legislative and institutional aspects and aspects of their performance situation and the need to finance SMEs in Romania through the European Structural Funds. Also, this article proposes a presentation of various reports and documents on the situation of SMEs in Romania and the European Union in recent years, with the emphasis on highlighting their importance and their contributions in the economic and social environment.